Public Opinion Research - Gaidys, Vladas; Tureikytė, Danutė (Sociologija. Mintis ir veiksmas, 1997)
The article discusses public opinion research, its historical development and methodological properties. Article begins with an overview of development of public opinion research. A lot of attention is given to the criterion of representativeness, whose importance was already evident in the early attempts to prognose the election results. The further and most important part of article contains the discussion of the structure public opinion research and its elements.
Keywords: public opinion; history; structure of public opinion research